Staging indigeneity salvage tourism and the performance of Native American history - Phillips, Katrina M. (Chapel Hill University of North Carolina Press, 2021)
"As tourists increasingly moved across the United States in the late nineteenth and early twentieth centuries, a surprising number of communities looked to capitalize on the histories of Native American people to create tourist attractions. From the Happy Canyon Indian Pageant and Wild West Show in Pendleton, Oregon, to outdoor dramas like 'Tecumseh!' in Chillicothe, Ohio, and 'Unto These Hills' in Cherokee, North Carolina, locals staged performances that claimed to honor an Indigenous past while depicting that past on white settlers' terms. Linking the origins of these performances to their present-day incarnations, this incisive book reveals how they constituted what Katrina Phillips calls 'salvage tourism' - a set of practices paralleling so-called salvage ethnography, which documented the histories, languages, and cultures of Indigenous people while reinforcing a belief that Native American societies were inevitably disappearing"
Days of old West are lived again : the Happy Canyon Indian Pageant and Wild West Show -- It's a part of us : the continued allure of Pendleton -- Out of the darkness of tragedy : the creation of "Unto these hills" -- We are telling our story : salvaging "Unto these hills" -- No longer a wooden Indian from the history books : tourism, Tecumseh, and American nationalism -- The great pretenders : playing Indian in "Tecumseh!"
Includes bibliographical references and index.
Keywords: Indians of North America -- Public opinion; Indians of North America -- History; Heritage tourism -- United States; Indian tourism -- United States; Pageants -- United States; Theater and nationalism -- United States; United States -- Historiography